Scleral Thickness in Human Eyes - Vurgese, Sujiv; Panda-Jonas, Songhomitra; Jonas, Jost B. (PLOS ONE, 2012)
Purpose To obtain information about scleral thickness in different ocular regions and its associations. Methods The histomorphometric study included 238 human globes which had been enucleated because of choroidal melanomas or due to secondary angle-closure glaucoma. Using light microscopy, anterior-posterior pupil-optic nerve sections were measured. Results In the non-axially elongated group (axial length ≤26 mm), scleral thickness decreased from the limbus (0.50±0.11 mm) to the ora serrata (0.43±0.14 mm) and the equator (0.42±0.15 mm), and then increased to the midpoint between posterior pole and equator (0.65±0.15 mm) and to the posterior pole (0.94±0.18 mm), from where it decreased to the peri-optic nerve region (0.86±0.21 mm) and finally the peripapillary scleral flange (0.39±0.09 mm). Scleral thickness was significantly lower in the axially elongated group (axial length >26 mm) than in the non-axially elongated group for measurements taken at and posterior to the equator. Scleral thickness measurements of the posterior pole and of the peripapillary scleral flange were correlated with lamina cribrosa thickness measurements. Scleral thickness measurements at any location of examination were not significantly (all P>0.10) correlated with corneal thickness measurements. Scleral thickness was statistically independent of age, gender and presence of glaucoma. Conclusions In non-axially elongated eyes, the sclera was thickest at the posterior pole, followed by the peri-optic nerve region, the midpoint between posterior pole and equator, the limbus, the ora serrata, the equator and finally the peripapillary scleral flange. In axially elongated eyes, scleral thinning occurred at and posterior to the equator, being more marked closer to the posterior pole and the longer the axial length was. Within the anterior and posterior segment respectively, scleral thickness measurements were correlated with each other. Posterior scleral thickness was correlated with lamina cribrosa thickness. Scleral thickness measurements at any location of examination were not significantly correlated with corneal thickness or with age, gender and presence of absolute secondary angler-closure glaucoma.